2002
DOI: 10.1016/s1044-0305(02)00375-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of lipooligosaccharides from Haemophilus ducreyi containing polylactosamine repeats

Abstract: Haemophilus ducreyi, a gram-negative human mucosal pathogen, is one of the principal causes of genital ulcer disease. The lipooligosaccharides (LOS) of these bacteria are considered to be a major virulence factor and have been implicated in the adherence and invasion of H. ducreyi to several human cell types. An isogenic heptosyltransferase-III knockout strain (waaQ) was recently constructed from H. ducreyi 35000 wild-type strain and immunochemical and molecular weight data of the isolated LOS suggested the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…However, the number of disaccharide repeats was limited to two or three (10). Analogous results were generated when the infectivity of Haemophilus ducreyi, a causative agent of genital ulcers, was studied; infectious strains made LOS with a few lactosamine repeats (4,22).…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…However, the number of disaccharide repeats was limited to two or three (10). Analogous results were generated when the infectivity of Haemophilus ducreyi, a causative agent of genital ulcers, was studied; infectious strains made LOS with a few lactosamine repeats (4,22).…”
mentioning
confidence: 86%
“…Sandlin and Stein (21) identified a strain of Neisseria sicca that expressed an unusual glycolipid that appeared based on sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) to be analogous to LPS made by enteric bacteria. A poly-N-acetyllactosamine repeat was seen in some strains of the gonococcus (10), and we postulated that the repeating carbohydrate found in N. sicca could be a variant of this structure.A few studies have shown that both Neisseria and Haemophilus strains have the ability to extend their LOS by adding lactosamine repeats to form polylactosamine; these strains seem to possess increased virulence (4,10,22). When N. gonorrhoeae MS11mkC was used to inoculate healthy male volunteers, 100% of the volunteers developed urethritis, compared to an infectivity rate of 40% for strains expressing a truncated LOS (23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Haemophilus ducreyi mutants lacking the enzymes heptosyltransferase III and b-(1 ! 4)-glucosyltransferase were shown to synthesize LOS with poly-Nacetyllactosamine repeats (Schilling et al, 2002a). The GlcNAc transferase from this species has been shown to be encoded by the lgtA gene (Sun et al, 2002).…”
Section: Lipopolysaccharides (Lps)mentioning
confidence: 99%
“…These include membranes such as those having a low molecular weight cut-off that can be used for drop dialysis (Schilling et al, 2001(Schilling et al, , 2002aYlönen et al, 2001;Post et al, 2002); resins, such as SP20SS (Huang et al, 2002), OASIS cartridges from Waters (Charlwood et al, 2000(Charlwood et al, , 2001aCharlwood, Skehel, & Camilleri, 2001b) (for 3-acetamido-6-aminoacridine (AA-Ac, 2/5) derivatives), H þ Dowex AG 50W X8 (for acidic xylo-oligosaccharides) (Kabel, Schols, & Voragen, 2002b) or Amberlite IR-120 (H þ ) (Janusch et al, 2002), anion-exchange ZipTips (for O-deacylated lipooligosaccharides) (Schilling et al, 2002a), or C18 ZipTips (Charlwood et al, 2001a;Charlwood, Skehel, & Camilleri, 2001b) from Millipore for AA-Ac-derivatized N-linked glycans. Various investigators have desalted lipopolysaccharides using Dowex 50W (Schilling et al, 2001(Schilling et al, , 2002aJones et al, 2002). Graphatized carbon is also proving to be an effective clean-up medium (Mills et al, 2001a,c).…”
Section: Clean-up Of Samples Prior To Maldi Analysismentioning
confidence: 99%